The association of dietary iron intake and serum iron with fecal incontinence: results from NHANES 2007–2010 - Li, Tingting; Cui, Jingxuan; Zhou, Yan; Yao, Qionglu; Cai, Lijun (Frontiers in Nutrition, 2025)
BackgroundThe relationship between iron and fecal incontinence (FI) is unclear. This study aims to explore the association between iron intake and serum iron levels and FI subtypes.Methods8,612 adults from the National Health and Nutrition Examination Survey 2007–2010 were included in the study. FI was determined by the Bowel Health Questionnaire. This study corrected for demographic characteristics, chronic diseases and so on.ResultsCompared to quartile 1, quartile 3 of dietary iron was associated with a higher risk of gas gut leakage (OR = 1.35, 95%CI:1.05–1.73), and quartile 4 of serum iron was associated with a lower risk of solid bowel leakage (OR = 0.42, 95%CI: 0.20–0.89). Restricted cubic spline (RCS) models showed an inverted U-shaped association between iron intake and the prevalence of gas gut leakage (P for nonlinear < 0.001). When iron intake is between 13.68 and 21.55 mg/day, the risk of gas gut leakage is significantly increased. However, serum iron was significantly negatively linearly correlated with solid stool leakage. Subgroup analysis suggested that there was heterogeneity in the association between iron and FI in terms of gender and age. The association is stronger in women and people aged 60 to 74 years. In exploratory analysis, higher ferritin levels in women of childbearing age were associated with a lower chance of mucus gut leakage.ConclusionLower serum iron levels and moderate iron intake may be associated with an increased risk of FI in adults, with gender and age differences. Older women may need to increase their iron intake, which may be beneficial in preventing FI. However, the causal relationship still needs to be verified by prospective studies.